2009
DOI: 10.1007/s00005-009-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of the family Legionellaceae

Abstract: The Legionellae are Gram-negative bacteria able to survive and replicate in a wide range of protozoan hosts in natural environments, but they also occur in man-made aquatic systems, which are the major source of infection. After transmission to humans via aerosols, Legionella spp. can cause pneumonia (Legionnaires' disease) or influenza-like respiratory infections (Pontiac fever). In children, Legionnaires' disease is uncommon and is mainly diagnosed in children with immunosuppression. The clinical picture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 139 publications
0
33
0
1
Order By: Relevance
“…Seven studies reported on the hazard of micro-organisms to HCWs and/or patients, see Table 5 study characteristics hazard in healthcare and the dental setting [12,31,34,45,[77][78][79] Three studies looked into the risks for patients when exposed to Legionella pneumophila containing sources that may produce bio-aerosols [34, 38,78]. They reported that cooling towers, air conditioning or mechanical ventilation systems could be a source of L. pneumophila.…”
Section: Hazard Of a Bio-aerosolmentioning
confidence: 99%
“…Seven studies reported on the hazard of micro-organisms to HCWs and/or patients, see Table 5 study characteristics hazard in healthcare and the dental setting [12,31,34,45,[77][78][79] Three studies looked into the risks for patients when exposed to Legionella pneumophila containing sources that may produce bio-aerosols [34, 38,78]. They reported that cooling towers, air conditioning or mechanical ventilation systems could be a source of L. pneumophila.…”
Section: Hazard Of a Bio-aerosolmentioning
confidence: 99%
“…Legionnaire's disease is a severe form of pneumonia. Pontiac fever is the most common clinical manifestation and causes typical symptoms with characteristics of influenza infection, including fever, chills, and headache following a short incubation period [5,8]. Pontiac fever is the most common clinical manifestation and causes typical symptoms with characteristics of influenza infection, including fever, chills, and headache following a short incubation period [5,8].…”
mentioning
confidence: 99%
“…This group contains with 84% of all infections the most important pathogenic Legionella [49]. Yet, since all Legionella species are regarded as potential pathogenic [40], a diagnostic test requires broad specificity to different Legionella serogroups and species. Thus, the specificity of a point of care test device needs to be extended to other subtypes, serogroups or species.…”
Section: Discussionmentioning
confidence: 99%